Revisiting postponement: the importance of cross-functional integration to understand tax implications in global supply chains - Norrman, Andreas; Prataviera, Lorenzo Bruno (Wiley, 2023)
As products and supply chains (SCs) evolve, logisticians must revisit their understanding of postponement. The postponement boundary problem acknowledges that value-adding operations’ timing and location in global SCs are critical decisions, impacted by taxes and government regulations in different jurisdictions. However, when combining hardware and software objects, software’s increasing importance heightens the implications of when and where value is added. Until now, postponement scholars mostly have overlooked fiscal/legal implications, and current research tied to the postponement boundary decision-making phenomenon has not considered hardware and software combination. Moreover, we lack understanding about how to make cross-functional decisions when interrelatedness between the logistics and fiscal/legal domains increases. We used an abductive approach to elaborate and contextualize postponement decision-making for global SCs of product offerings that combine hardware and software objects. A single-case study (with four subcases) was used to explore postponement decisions (and related fiscal and legal implications) and cross-functional integration (CFI) at a global high-tech enterprise. We also elaborated on the contextual drivers of increased postponement boundary complexity to illustrate changes in its decision-making. We also emphasized formalized boundary objects’ importance in enhancing CFI by developing formal steering documents, creating interdependent organizational structures, and aligning trade-offs and outcomes.
Keywords: boundary object; cross-functional integration; global supply chains; operating model; postponement boundary problem; software supply; tax implications